Assessment of body posture of boys aged 7-15 in relation to the body mass index – BMI - Lubkowska, Wioletta; Mroczek, Bożena (Journal of Education, Health and Sport, 2017)
Introduction. The problem of growing incidence of bad posture in children and adolescents is so significant that it has become an important social problem. One of reasons behind higher incidence of abnormal posture may be underweight, overweight or obesity. Objectives. Evaluation of incidence of bad posture in boys aged 7-15, including the Body Mass Index (BMI). Material and methods. The study included 511 boys aged 7-15 from Szczecin. Each age group consisted of approx. 50-70 children. Posture was assessed with the spherosomatometric method. Physiological curvature of the spine in the sagittal plane were determined. Next, normative values for anterior-posterior spinal curvatures were used to determine the incidence of bad posture. Based on logistic regression, the parameters of the logit model were assessed, taking into account subjects’ age and BMI. Results. In the entire population, bad posture was identified in 32.48% of subjects. Age did not differentiate the incidence of bad posture in terms of statistical significance. Boys with incorrect BMI amounted to 28.37% of all subjects. Underweight was observed in 6.96% of subjects. 7.54% of subjects were overweight and 2.03% obese, which gave a total of 9.57% of the researched population. The increase in BMI correlated with higher chances of bad posture by almost 25%, while age was a variable which reduced the risk of bad posture by almost 15%. Conclusions. Incorrect BMI predisposed subjects to bad posture. High proportion of children with bad posture justify the need to promote preventive and corrective measures. The increasing proportion of overweight and obese children should serve as a motivator to shape healthy behaviors of students and parents, as well as schools and the medical environment.